Secondary battery and electric device
By adding specific additives to the electrolyte of lithium-ion batteries and forming an SEI film containing ethoxy groups and lithium nitride on the surface of the negative electrode active material layer, the problem that the battery is difficult to take into account both fast charging and circulation performance in high and low temperature environments, achieving a longer cycle life and higher safety.
Patent Information
- Application Number
- CN202510024396.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
When faced with high and low temperature environments, it is difficult to take into account fast charging and circulation performance, and the use of carboxylate solvents poses a threat to high temperature safety and cycle life.
By adding ethoxy compound and nitrogen-containing additive to the electrolyte, and forming a solid electrolyte interface film (SEI film) on the surface of the negative electrode active material layer, the film contains ethoxy compound and lithium nitride, and its weight percentage content is controlled by X-ray photoelectron spectrometer test to achieve the density and flexibility of the SEI film.
It improves the fast charging and low-temperature performance of lithium-ion batteries, extends the cycle life of the battery, especially the cycle life and storage performance at high temperatures, while enhancing the safety of the battery.
Smart Images

Figure BDA0005232325680000021 
Figure BDA0005232325680000031 
Figure BDA0005232325680000032
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries. Specifically, the present application relates to a secondary battery and an electrical device. Background Art
[0002] Lithium-ion batteries, with their superior energy density, excellent cycle life and no memory effect, have become an indispensable energy supplier for 3C products such as mobile phones and laptops. They also occupy a core position in the field of electric vehicles, driving the trend of green travel. In recent years, electric vehicles have made significant progress in energy density, cycle performance, safety and cost control, and lithium-ion batteries have made an indispensable contribution. However, the long charging time of electric vehicles has limited their widespread popularity and application in the market. Breakthroughs in fast charging technology are crucial to the future development of electric vehicles. It can not only shorten the waiting time for charging and improve user experience, but also accelerate the market penetration of electric vehicles and promote the green energy revolution.
[0003] However, existing commercial lithium-ion batteries have difficulty balancing fast charging and cycle performance when facing performance challenges in high and low temperature environments. In order to improve fast charging capabilities and low temperature adaptability, existing technologies tend to use low-boiling point carboxylic acid ester solvents to reduce the viscosity of the electrolyte and increase ionic conductivity. However, although this approach improves certain performance indicators of the battery in the short term, in the long run, it poses a serious threat to the high temperature safety and cycle life of the battery. Moreover, the frequent side reactions of carboxylic acid ester solvents with negative electrode materials not only reduce the high temperature safety performance of the battery, but also aggravate the internal loss of the battery and shorten its service life.
[0004] Therefore, finding a solution that can meet the needs of fast charging, keep the battery working stably under extreme temperatures, and extend the battery cycle life has become one of the urgent tasks for technical researchers. Summary of the invention
[0005] The main purpose of the present invention is to provide a secondary battery and an electrical device, especially a fast-charging and long-life secondary battery and an electrical device, so as to solve the problem in the prior art that it is difficult for batteries to simultaneously take into account high temperature performance, low temperature performance, fast charging and cycle performance.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a secondary battery is provided, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises an ethoxy-containing additive and a nitrogen-containing additive; the negative electrode comprises a negative electrode active material layer, and a solid electrolyte interface film located on the surface of the negative electrode active material layer, wherein the solid electrolyte interface film comprises an ethoxy compound and lithium nitride, wherein the ethoxy compound is derived from the ethoxy-containing additive, and the lithium nitride is derived from the nitrogen-containing additive; and the weight percentage of the oxygen element derived from the ethoxy compound in the solid electrolyte interface film is defined as W by using an X-ray photoelectron spectrometer. O %, the weight percentage of nitrogen from lithium nitride in the solid electrolyte interface film is defined as W N %, among which 3≤2W O +W N ≤10. Under the above conditions, the lithium nitride and ethoxy compounds in the SEI film have a good synergistic effect, wherein lithium nitride improves ion transport, and ethoxy compounds can improve the flexibility of the SEI film, improve the structural stability of the interface film of the electrode during fast charging, improve the kinetic characteristics of lithium ion transmission at the interface, reduce impedance, and improve the fast charging performance and low temperature performance of the battery; it can also further improve the density and flexibility of the SEI film, thereby effectively inhibiting the rupture of the SEI film during high-temperature cycling, thereby helping to reduce the negative effects of continuous side reactions between the electrolyte and the negative electrode, and extend the cycle performance of the secondary battery, especially the cycle life and storage performance at high temperatures.
[0007] Furthermore, 0.05<W O <5, preferably, 1≤W O ≤3; Under the above conditions, it can more effectively promote the formation of a stable and flexible SEI film, which is more conducive to improving the fast charging performance and cycle stability of lithium-ion batteries; and / or, 1<W N <10, preferably, 2≤W N ≤8. Under the above conditions, the lithium ion conductivity and high temperature stability of the SEI film can be further enhanced, which is more conducive to improving the fast charging capability and cycle life of the battery.
[0008] Furthermore, the tortuosity of the negative electrode is defined as τ, where 0 < 2 (W N ×W O )-τ<1. Under the above conditions, the lithium ion conductivity in the electrode is faster, the electrolyte can penetrate into the gap more fully, and there are fewer side reactions between the electrodes, so that the high temperature performance, low temperature performance, fast charging and cycle performance of the battery can be more effectively taken into account, and the overall performance of the battery is better.
[0009] Furthermore, 2.5<τ<9. Under the above conditions, the ion transmission path of the secondary battery is shorter, the transmission efficiency is faster, the current distribution is more uniform, the SEI film is more stable, the generated heat is dissipated faster, and the mechanical stability and chemical stability are better. The high temperature performance, low temperature performance, fast charging and cycle performance of the battery are better.
[0010] Further, the ethoxy-containing additive includes one or more of ethoxy acrylate, ethoxy vinylene carbonate and ethoxy vinylene sulfite; preferably, the ethoxy acrylate has a structure shown in the general formula (I-1):
[0011]
[0012] In the general formula (I-1), n is an integer from 1 to 4, and R 11 is selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate, R 12 Selected from hydrogen, C1-C3 alkyl;
[0013] Preferably, ethoxy vinylene carbonate has a structure shown in general formula (I-2):
[0014]
[0015] In the general formula (I-2), m is an integer from 1 to 4, and R 13 Selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate;
[0016] Preferably, ethoxy vinylene sulfite has a structure shown in general formula (I-3):
[0017]
[0018] In the general formula (I-3), p is an integer from 1 to 4, and R 14 Selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate; the ethoxy-containing additive having the above structure can significantly enhance the transmission of lithium ions, further improve the flexibility of the SEI film, and enhance the structural stability of the interface film of the electrode during fast charging;
[0019] and / or, the nitrogen-containing additive includes one or more of nitrile compounds, phosphazenes, amides, organic nitrogen-containing lithium salts, inorganic nitrogen-containing alkali metal salts, nitrate esters and nitroesters;
[0020] Preferably, the nitrile compound has a structure represented by the general formula (II-1):
[0021]
[0022] In the general formula (II-1), R 21is selected from C2-C10 alkylene or nitrile-substituted C2-C10 alkylene, R 22 is selected from hydrogen, nitrile, C1-C6 alkyl or carboxylate;
[0023] Preferably, the phosphazene has a structure shown in the general formula (II-2):
[0024]
[0025] In the general formula (II-2), R 23 is selected from C1-C6 alkyl or fluorinated C1-C6 alkyl, R 24 , R 25 , R 26 , R 27 and R 28 are independently selected from hydrogen, fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 24 , R 25 , R 26 , R 27 and R 28 At least one of them is fluorine or fluorinated C1-C6 alkyl;
[0026] Preferably, the amide has a structure represented by the general formula (II-3):
[0027]
[0028] In the general formula (II-3), R 29 , R 210 , R 211 are independently selected from hydrogen, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 29 , R 210 , R 211 At least one of them is a fluorinated C1-C6 alkyl group;
[0029] Preferably, the organic nitrogen-containing lithium salt has a structure represented by the general formula (II-4) or the general formula (II-5):
[0030]
[0031] In the general formula (II-4), R 212 , R 213 , R 214 are independently selected from hydrogen, fluorine, C1-C6 alkyl, fluorinated C1-C6 alkyl or nitrile, and R 212 , R 213 , R 214 At least one of them is selected from fluorine, fluorinated C1-C6 alkyl or nitrile;
[0032]
[0033] In the general formula (II-5), R 215 , R 216 are independently selected from fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 215 and R 216 At least one of them is selected from fluorine or fluorinated C1-C6 alkyl;
[0034] Preferably, the inorganic nitrogen-containing alkali metal salt has a structure shown in the general formula (II-6):
[0035] R 217 NO t General formula (II-6);
[0036] In the general formula (II-6), t is selected from 2 or 3; R 217 Selected from lithium, sodium or potassium;
[0037] Preferably, the nitrate ester has a structure shown in the general formula (II-7):
[0038] R 218 NO r General formula (II-7);
[0039] In the general formula (II-7), r is 3; R 218 Selected from C1-C4 alkyl;
[0040] Preferably, the nitroester has a structure shown in the general formula (II-8):
[0041] R 219 NO r General formula (II-8);
[0042] In the general formula (II-8), s is 2; R 219 The nitrogen-containing additive having the above structure can further improve the lithium ion transportability and structural stability of the SEI film at high temperature, thereby being more conducive to improving the fast charging performance and high temperature cycle storage performance of the negative electrode.
[0043] Further, the ethoxy acrylate includes one or more of ethoxyethoxyethyl acrylate, 2-methoxyethyl acrylate and triethylene glycol diacrylate; and / or, the ethoxy vinylene carbonate includes one or more of methylethoxy vinylene carbonate, methylethoxy vinylene sulfite and methoxyethoxymethyl vinylene carbonate; and / or, the ethoxy vinylene sulfite includes ethoxymethyl vinylene sulfite; and / or, the nitrile compound includes one or more of succinonitrile, adiponitrile, glutaronitrile, hexanetrinitrile, ethylene glycol (bis) propionitrile ether, methoxypropionitrile, 2,3-dimethoxypropionitrile and methyl cyanoacetate; and / or, the phosphazene includes methoxypentafluorocyclotriphosphazene , trifluoromethoxypentafluorocyclotriphosphazene, ethoxypentafluorocyclotriphosphazene and trifluoroethoxypentafluorocyclotriphosphazene; and / or, amides include trifluoroformamide or trifluoroacetamide; and / or, organic nitrogen-containing lithium salts include one or more of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium, (fluorosulfonyl)(perfluorobutylsulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium, bistrifluoromethylsulfonylimide lithium and bis(pentafluoroethylsulfonic acid)imide lithium; and / or, inorganic nitrogen-containing alkali metal salts include one or more of lithium nitrate, lithium nitrite, sodium nitrate and sodium nitrite; and / or, nitrate esters include ethyl nitrate and / or propyl nitrate; and / or, nitroesters include nitromethane and / or nitroethane. The above-mentioned specific types of ethoxy-containing additives and nitrogen-containing additives can work synergistically, which is more conducive to constructing a dense, flexible, and highly ion-conductive SEI film, thereby significantly reducing side reactions during fast charging and improving the performance of the battery in high and low temperature environments.
[0044] Furthermore, in the electrolyte, the weight percentage of the ethoxylated additive is 0.05-4%; and / or, in the electrolyte, the weight percentage of the nitrogen-containing additive is 0.5-10%; preferably, the weight ratio of the ethoxylated additive to the nitrogen-containing additive is (0.05-4):1. Under the above conditions, the ethoxylated additive and the nitrogen-containing additive can further optimize the SEI film structure, which is more conducive to improving the fast charging performance and cycle stability of the battery, while maintaining good safety and electrochemical efficiency.
[0045] Furthermore, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and lithium bis(fluorosulfonyl)imide, the weight ratio of which is (0.05-4):1; or, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and ethoxypentafluorocyclotriphosphazene, the weight ratio of which is (2-4):1; or, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and ethyl nitrate, the weight ratio of which is (1-4):1. The above-mentioned combination of electrolyte additives works synergistically, which is more conducive to constructing a SEI membrane with both high lithium ion transport and structural stability, thereby being able to more significantly improve the fast charging capability and high temperature cycle performance of the secondary battery, reduce gas production, and enhance the safety of the battery.
[0046] Further, the electrolyte also includes other additives, and the other additives include one or more of vinylene carbonate, vinyl ethylene carbonate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, 2,2,2-trifluoromethyl ethyl carbonate, 2,2,2-trifluorodiethyl carbonate, tris(trifluoroethyl)phosphate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether; the electrolyte The weight percentage of other additives is 0.1-10%; the above-mentioned other additives can participate in the formation of SEI film, cooperate with ethoxy-containing additives and nitrogen-containing additives to construct a composite SEI film, which is more conducive to maintaining the structural integrity of the SEI film during fast charging, thereby further reducing electrolyte consumption and improving battery cycle life and safety; and / or, the positive electrode includes a positive electrode active material, the positive electrode active material includes a lithium nickel transition metal oxide, and the chemical formula of the lithium nickel transition metal oxide is: LiNi x Co y A (1-x-y) O2, wherein A includes one or more of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the stable and highly conductive interface layer formed by the additive of the present application can more effectively slow down the structural degradation of the above-mentioned positive electrode material during the charging and discharging process, thereby further extending the cycle life of the battery; and / or, the negative electrode active material in the negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon, silicon alloys, silicon oxides and silicon carbon compounds; preferably, in the negative electrode active material, the weight percentage of the silicon-based material is 10-100%, and the additive of the present application can interact with the above-mentioned negative electrode active material to form a more stable SEI film, protect the negative electrode material from being eroded by the electrolyte, more effectively buffer the volume change of the silicon-based material during the charging and discharging process, and improve the conductivity of the negative electrode, thereby being more conducive to improving the charging and discharging efficiency, cycle stability and safety of the battery.
[0047] According to another aspect of the present invention, there is provided an electric device, comprising the above-mentioned secondary battery. The electric device using the secondary battery of the present application can enhance the fast charging and cycle performance of the electric device through the optimized SEI film, significantly improve the overall energy density, power output and durability, and is suitable for application scenarios requiring high energy, fast charging and long-term stable operation.
[0048] The present invention controls the type of electrolyte in the secondary battery, and controls the content of nitrogen and oxygen in the solid electrolyte interface film (SEI film) formed on the surface of the negative electrode active material layer within a specific range. The nitrogen from the nitrogen-containing additive improves the lithium ion transportability and structural stability of the SEI film at high temperature, thereby improving the fast charging performance and high-temperature cycle storage performance of the negative electrode; the oxygen from the ethoxy-containing additive exists in the form of -(CH2-CH2O)-, which improves the transmission of lithium ions and improves the flexibility of the SEI film, thereby ensuring the structural stability of the interface film of the electrode during fast charging. Moreover, the nitrogen-containing compound and the ethoxy-containing compound have a good synergistic effect in structure, improve the kinetic characteristics of lithium ion transmission at the interface, reduce impedance, and improve the fast charging performance and low temperature performance of the battery; further improve the density and flexibility of the SEI film, thereby effectively inhibiting the rupture of the SEI film during high-temperature cycling, thereby reducing the negative effects such as the continuous side reaction of the electrolyte and the negative electrode, and extending the cycle performance of the secondary battery, especially the cycle life and storage performance at high temperature.
[0049] Based on the above improvements, the SEI film in the secondary battery of the present invention is dense and stable, which effectively inhibits the continuous decomposition and gas production of the electrolyte. The secondary battery has excellent fast charging performance. At the same time, it has good cycle performance, storage performance and safety performance at high and low temperatures. DETAILED DESCRIPTION
[0050] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0051] For the sake of simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0052] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0053] A list of items connected by the term "one or more of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "one or more of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "one or more of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0054] As described in the background of the present invention, there is a problem in the prior art that it is difficult for batteries to simultaneously take into account high temperature performance, low temperature performance, fast charging and cycle performance. In order to solve the above problems, in a typical embodiment of the present invention, a secondary battery is provided, including a positive electrode, a negative electrode and an electrolyte, the electrolyte including an ethoxy-containing additive and a nitrogen-containing additive; the negative electrode includes a negative electrode active material layer, and a solid electrolyte interface membrane located on the surface of the negative electrode active material layer, the solid electrolyte interface membrane contains an ethoxy compound and lithium nitride, the ethoxy compound is derived from the ethoxy-containing additive, and the lithium nitride is derived from the nitrogen-containing additive; using an X-ray photoelectron spectrometer to test, the weight percentage of oxygen from the ethoxy compound in the solid electrolyte interface membrane is defined as W O %, the weight percentage of nitrogen from lithium nitride in the solid electrolyte interface film is defined as W N %, among which 3≤2W O +W N ≤ 10. In some embodiments, 4≤2O+N≤8.
[0055] In the solid electrolyte interface film SEI on the surface of the negative electrode, the nitrogen element from the nitrogen-containing additive can form lithium nitride to improve the lithium ion transportability of the SEI film and the structural stability at high temperature, which is beneficial to improve the fast charging performance and high-temperature cycle storage performance of the negative electrode; however, due to the high activity of the nitrogen element, when its content is high, it will affect the initial efficiency and capacity of the electrode; and the nitrogen element usually exists in the form of Li3N, which has low adhesion to the electrode. During fast charging, the change in the electrode volume can easily cause the SEI to rupture, thereby affecting the electrochemical performance of the battery.
[0056] In the solid electrolyte interface film SEI on the surface of the negative electrode, the oxygen element from the ethoxy-containing additive exists in the form of -(CH2-CH2O)-, which can enhance the transmission of lithium ions, improve the flexibility of the SEI film, and improve the structural stability of the interface film during fast charging of the electrode; however, when its content is too high, the swelling rate of the SEI film on the surface of the negative electrode active material layer is too high, resulting in an unstable interface film structure, thereby increasing the side reactions of the electrolyte on the negative electrode side, and ultimately deteriorating the cycle life of the battery.
[0057] The inventors have found through a large number of experimental verifications and theoretical studies that the contents of nitrogen and oxygen meet the requirements of "3≤2W O +W N When the SEI film is less than or equal to 10", the SEI film is dense and stable, which can effectively inhibit the continuous decomposition of the electrolyte caused by the contact between the electrolyte and the negative electrode active material, and inhibit the gas production, thereby improving the cycle performance and safety performance of the secondary battery, especially the cycle performance and storage performance at high temperature.
[0058] In addition, the lithium nitride and ethoxy compounds in the SEI film have a good synergistic effect. Lithium nitride improves ion transport, and ethoxy compounds can improve the flexibility of the SEI film, improve the structural stability of the interface film of the electrode during fast charging, and improve the kinetic characteristics of lithium ion transmission at the interface, reduce impedance, and improve the fast charging performance and low-temperature performance of the battery; it can also further improve the density and flexibility of the SEI film, thereby effectively inhibiting the rupture of the SEI film during high-temperature cycling, which is beneficial to reduce the negative effects such as continuous side reactions between the electrolyte and the negative electrode, and extend the cycle performance of the secondary battery, especially the cycle life and storage performance at high temperatures.
[0059] Based on the above improvements, the secondary battery of the present application has excellent fast charging performance, and at the same time, has good cycle performance, storage performance and safety performance at high and low temperatures.
[0060] Typical but not limiting, 2W O +W N The value is 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range of any two values.
[0061] The inventors further preferred W O and W N In a preferred embodiment, 0.05<W O <5, preferably, 0.5≤W O ≤4, more preferably, 1≤W O ≤3. Typical but not limiting, W Ois 0.1, 0.2, 0.5, 0.8, 1, 1.1, 1.3, 1.4, 1.5, 1.6, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 4.9 or a range consisting of any two values. Under the above conditions, it can more effectively promote the formation of a stable and flexible SEI film, which is more conducive to improving the fast charging performance and cycle stability of lithium-ion batteries. However, W O Too low or too high may lead to poor SEI film structure, thus affecting the transmission of lithium ions and battery performance, especially under fast charging and high-temperature cycling conditions, which may accelerate battery degradation.
[0062] In a preferred embodiment, 1<W N <10, preferably, 2≤W N ≤8. In a preferred embodiment, 2≤W N ≤6. In a preferred embodiment, 3≤W N ≤6. Typical but not limiting, W N is 1.6, 1.7, 2, 2.3, 2.5, 2.7, 3, 3.3, 3.5, 3.7, 4, 4.3, 4.5, 4.8, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or a range consisting of any two values. Under the above conditions, the lithium ion conductivity and high temperature stability of the SEI film can be further enhanced, which is more conducive to improving the fast charging capability and cycle life of the battery. However, if W N If W is too low, it may not be enough to optimize the SEI film. N If it is too high, it may induce additional side reactions and even damage the battery performance, especially the first efficiency and electrochemical stability at high temperature.
[0063] Tortuosity is a parameter that reflects the degree of tortuosity of the path from one end to the other end of the pores in the porous medium relative to the straight line, that is, the ratio of the actual flow path length to the straight-line distance between the ends of the flow path. In the electrode structure, the electrolyte fully infiltrates into the pores, and the transmission of lithium ions needs to migrate along the pores through the electrolyte. Therefore, the electrode tortuosity has an important influence on the lithium ion conductivity and electrolyte diffusion in the electrode. It is also of great significance to the construction of the relationship between the battery performance and the interface composition of the electrode and the electrode structure characteristics. In this application, the tortuosity can be adjusted according to the characteristics of the selected negative electrode active material by conventional technical means in the field, such as controlling the electrode rolling pressure, rolling temperature, rolling speed and number of rolling times.
[0064] In a preferred embodiment, the tortuosity of the negative electrode is defined as τ, where 0<2(W N ×WO )-τ<1;Preferably, 0.2≤2(W N ×W O )-τ≤0.8; more preferably, 0.3≤2(W N ×W O )-τ≤0.6. Under the above conditions, the lithium ion conductivity in the electrode is faster, the electrolyte can more fully penetrate into the gap, and there are fewer side reactions between the electrodes, so that the battery's high temperature performance, low temperature performance, fast charging and cycle performance can be more effectively taken into account, and the overall performance of the battery is better. When 2(W N ×W O )-τ value is too large, correspondingly, the nitrogen and oxygen content in the SEI film is too high, or the tortuosity of the negative electrode is too small, which may increase the reaction between the electrolyte and the electrode, thereby increasing the electrolyte consumption, reducing the battery cycle life, and may also increase the battery gas production. N ×W O )-τ value is too small, and accordingly, the content of nitrogen and oxygen in the SEI film is too low, or the tortuosity of the negative electrode plate is large, which may lead to reduced wettability of the negative electrode electrolyte, resulting in poor kinetics, increased polarization, and reduced capacity of the secondary battery during the cycle, thus affecting its electrochemical performance. Typical but not limiting, 2(W N ×W O )-τ value is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or a range consisting of any two values.
[0065] In a preferred embodiment, 2.5<τ<9; preferably, 3<τ<8; more preferably, 4<τ<7. Typically but not limiting, the τ value is 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.8 or a range consisting of any two values. If the negative electrode plate tortuosity is too large, it may cause uneven heat dissipation inside the battery, aggravate the expansion problem of the electrode material, affect the stability and safety of the battery under high temperature conditions, and may also cause low ion mobility, long ion transmission path, and increased resistance, resulting in poor charging and discharging performance at low temperature. In addition, it may also cause uneven current distribution, and the heat generated during fast charging is difficult to dissipate quickly, thereby affecting the fast charging performance and safety of the battery, and may affect the stability of the SEI film on the surface of the negative electrode, thereby affecting the cycle life of the battery. If the negative electrode plate tortuosity is too small, it will also affect the life, electrochemical performance and safety of the battery. Under the above conditions, the ion transmission path of the secondary battery is shorter, the transmission efficiency is faster, the current distribution is more uniform, the SEI film is more stable, the generated heat is dissipated faster, and at the same time the mechanical stability and chemical stability are better. The battery's high temperature performance, low temperature performance, fast charging and cycle performance are better.
[0066] In a preferred embodiment, the ethoxy-containing additive includes one or more of ethoxy acrylate, ethoxy vinylene carbonate and ethoxy vinylene sulfite. The above oxygen-containing additive can more effectively improve the flexibility of the SEI film and the lithium ion conduction efficiency, thereby being more conducive to enhancing the fast charging performance and cycle stability of the battery; moreover, it can cooperate with the nitrogen-containing additive to jointly optimize the SEI film structure, thereby more significantly inhibiting the occurrence of side reactions and extending the battery life.
[0067] Preferably, the ethoxy acrylate has a structure shown in the general formula (I-1):
[0068]
[0069] In the general formula (I-1), n is an integer from 1 to 4, and R 11 is selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate, such as H, C2H5 or vinyl propionate, R 12 Selected from hydrogen, C1-C3 alkyl, such as H, CH3 or C2H5.
[0070] Preferably, ethoxy vinylene carbonate has a structure shown in general formula (I-2):
[0071]
[0072] In the general formula (I-2), m is an integer from 1 to 4, and R 13is selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate, such as H, C2H5 or vinyl propionate;
[0073] Preferably, ethoxy vinylene sulfite has a structure shown in general formula (I-3):
[0074]
[0075] In the general formula (I-3), p is an integer from 1 to 4, and R 14 Selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate.
[0076] The ethoxy-containing additive having the above structure can more significantly enhance the transmission of lithium ions, further improve the flexibility of the SEI film, and enhance the structural stability of the interface film of the electrode during fast charging.
[0077] In a preferred embodiment, the nitrogen-containing additive includes one or more of nitrile compounds, phosphazenes, amides, organic nitrogen-containing lithium salts, inorganic nitrogen-containing alkali metal salts, nitrates and nitroesters. The above nitrogen-containing additives can further improve the ionic conductivity of the electrolyte, improve the composition and structure of the interface film, and make it more effectively exert the above effects, thereby further improving the fast charging performance and cycle storage performance of the secondary battery.
[0078] Preferably, the nitrile compound has a structure represented by the general formula (II-1):
[0079]
[0080] In the general formula (II-1), R 21 is selected from C2-C10 alkylene or nitrile-substituted C2-C10 alkylene, more preferably, R 21 is selected from C1-C6 alkylene or C2-C6 alkylene substituted with a nitrile group, such as ethylene, propylene, butylene, pentylene, hexylene, or ethylene, propylene, butylene, pentylene, hexylene substituted with a nitrile group; R 22 is selected from hydrogen, nitrile, C1-C6 alkyl or carboxylate, more preferably, R 22 Selected from hydrogen, C1-C6 alkyl, or nitrile.
[0081] Preferably, the phosphazene has a structure shown in the general formula (II-2):
[0082]
[0083] In the general formula (II-2), R 23 is selected from C1-C6 alkyl or fluorinated C1-C6 alkyl, R 24 , R 25 , R 26 , R27 and R 28 are independently selected from hydrogen, fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 24 , R 25 , R 26 , R 27 and R 28 At least one of them is fluorine or fluorinated C1-C6 alkyl; more preferably, R 23 is selected from C1-C4 alkyl or fluorinated C1-C4 alkyl, R 24 , R 25 , R 26 , R 27 and R 28 are independently selected from fluorine, C1-C4 alkyl or fluorinated C1-C4 alkyl, or R 28 is selected from methyl, ethyl, n-propyl, isopropyl, trifluoromethyl or 2,2,2-trifluoroethyl, R 23 , R 24 , R 25 , R 26 , R 27 are independently selected from fluorine or fluorinated C1-C4 alkyl, and R 23 , R 24 , R 25 , R 26 and R 27 At least one of them is fluorine.
[0084] Preferably, the amide has a structure represented by the general formula (II-3):
[0085]
[0086] In the general formula (II-3), R 29 , R 210 , R 211 are independently selected from hydrogen, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 29 , R 210 , R 211 At least one of them is a fluorinated C1-C6 alkyl group; more preferably, R 29 , R 210 , R 211 are independently selected from hydrogen, C1-C4 alkyl or fluorinated C1-C4 alkyl, and R 29 , R 210 , R 211 At least one of them is a fluorinated C1-C4 alkyl group.
[0087] Preferably, the organic nitrogen-containing lithium salt has a structure represented by the general formula (II-4) or the general formula (II-5):
[0088]
[0089] In the general formula (II-4), R 212 , R 213 , R 214 are independently selected from hydrogen, fluorine, C1-C6 alkyl, fluorinated C1-C6 alkyl or nitrile, and R 212 , R 213 , R 214 At least one of them is selected from fluorine, fluorinated C1-C6 alkyl or nitrile; more preferably, R 212 , R 213 , R 214 are independently selected from fluorine or fluorinated C1-C4 alkyl, and R 212 , R 213 , R 214 At least one of them is a nitrile group;
[0090]
[0091] In the general formula (II-5), R 215 , R 216 are independently selected from fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 215 and R 216 At least one of them is selected from fluorine or fluorinated C1-C6 alkyl; more preferably, R 215 , R 216 are independently selected from fluorine, C1-C4 alkyl or fluorinated C1-C4 alkyl, and R 215 and R 216 At least one of them is selected from fluorine or fluorinated C1-C4 alkyl.
[0092] Preferably, the inorganic nitrogen-containing alkali metal salt has a structure shown in the general formula (II-6):
[0093] R 217 NO t General formula (II-6);
[0094] In the general formula (II-6), t is selected from 2 or 3; R 217 Selected from lithium, sodium or potassium.
[0095] Preferably, the nitrate ester has a structure shown in the general formula (II-7):
[0096] R 218 NO r General formula (II-7);
[0097] In the general formula (II-7), r is 3; R 218 Selected from C1~C4 alkyl.
[0098] Preferably, the nitroester has a structure shown in the general formula (II-8):
[0099] R 219 NO s General formula (II-8);
[0100] In the general formula (II-8), s is 2; R 219 Selected from C1~C4 alkyl.
[0101] The nitrogen-based additive having the above structure can further improve the lithium ion transportability and structural stability of the SEI film at high temperatures, thereby being more conducive to improving the fast charging performance and high-temperature cycle storage performance of the negative electrode.
[0102] The inventors further optimized the composition and types of ethoxy-containing additives and nitrogen-containing additives. In a preferred embodiment, the ethoxy acrylate includes one or more of ethoxyethoxyethyl acrylate EOEA, 2-methoxyethyl acrylate MOEA and triethylene glycol diacrylate TGD; and / or, the ethoxy vinylene carbonate includes one or more of methylethoxy vinylene carbonate, methylethoxy vinylene sulfite and methoxyethoxymethyl vinylene carbonate; and / or, the ethoxy vinylene sulfite includes ethoxymethyl vinylene sulfite. The above ethoxy compounds have rich -(CH2O-CH2O) n -structure, which can further improve the flexibility and lithium ion conductivity of the SEI film, thereby more effectively inhibiting the decomposition of the electrolyte and extending the battery life.
[0103] In a preferred embodiment, the nitrile compound includes one or more of succinonitrile SN, adiponitrile ADN, glutaronitrile GLN, hexanetrinitrile HTN, ethylene glycol (bis) propionitrile ether DENE, methoxypropionitrile MOPN, 2,3-dimethoxypropionitrile DMOPN and methyl cyanoacetate MOCA; and / or, the phosphazene includes one or more of methoxypentafluorocyclotriphosphazene, trifluoromethoxypentafluorocyclotriphosphazene, ethoxypentafluorocyclotriphosphazene PFPN and trifluoroethoxypentafluorocyclotriphosphazene TFPN; and / or, the amide includes trifluoroformamide or trifluoroacetamide; and / or, the organic nitrogen-containing lithium salt includes 4,5-difluoro-1,2 ... -dicyano-2-(trifluoromethyl)imidazole) lithium LiTDI, (fluorosulfonyl) (perfluorobutylsulfonyl) imide lithium LiFNFSI, bis(fluorosulfonyl) imide lithium LiFSI, bistrifluoromethylsulfonyl imide lithium LiTFSI and bis(pentafluoroethylsulfonic acid) imide lithium LiBETI; and / or, inorganic nitrogen-containing alkali metal salts include one or more of lithium nitrate LiNO3, lithium nitrite LiNO2, sodium nitrate NaNO3 and sodium nitrite NaNO2; and / or, nitrate esters include ethyl nitrate and / or propyl nitrate; and / or, nitroesters include nitromethane and / or nitroethane. The above nitrogen-containing compounds are more conducive to the formation of compounds such as Li3N, thereby being more conducive to enhancing the thermal stability of the membrane and the lithium ion transmission rate.
[0104] The above-mentioned specific types of ethoxy-containing additives and nitrogen-containing additives can work synergistically, which is more conducive to constructing a dense, flexible, and highly ion-conductive SEI film, thereby significantly reducing side reactions during fast charging and improving the performance of the battery in high and low temperature environments.
[0105] After a large number of experiments, the inventors have optimized the content range of ethoxy-containing additives and nitrogen-containing additives. In a preferred embodiment, the weight percentage of the ethoxy-containing additive in the electrolyte is 0.05-4%, preferably 0.2-3%; and / or, the weight percentage of the nitrogen-containing additive in the electrolyte is 0.5-10%, preferably 1-5%. In a preferred embodiment, the weight ratio of the ethoxy-containing additive to the nitrogen-containing additive is (0.05-4):1. Under the above conditions, the ethoxy-containing additive and the nitrogen-containing additive can further optimize the SEI film structure, which is more conducive to improving the fast charging performance and cycle stability of the battery, while maintaining good safety and electrochemical efficiency. If the ethoxy-containing additive is too high, the swelling rate of the SEI film on the surface of the negative electrode active material layer may be too high, resulting in an unstable interface film structure, thereby increasing the side reactions of the electrolyte on the negative electrode side, and ultimately deteriorating the cycle life of the battery. If the content of ethoxylated additives is too low, the improvement effect on the SEI film may not be obvious; if the content of nitrogen-containing additives is too high, the initial efficiency and capacity of the electrode may decrease, and the nitrogen element usually exists in the form of Li3N, which has low adhesion to the electrode. During fast charging, the change in electrode volume can easily lead to the rupture of SEI, thereby affecting the electrochemical performance of the battery. If the content of nitrogen-containing additives is too low, it may also lead to poor improvement of the SEI film.
[0106] Typically but not limiting, in the electrolyte, the weight percentage of the ethoxylated additive is 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4% or a range consisting of any two values, and the weight percentage of the nitrogen-containing additive is 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two values; the weight ratio of the ethoxylated additive to the nitrogen-containing additive is 0.05:1, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1 or a range consisting of any two values.
[0107] In a preferred embodiment, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and lithium bis(fluorosulfonyl)imide, the weight ratio of which is (0.05-4):1; or, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and ethoxypentafluorocyclotriphosphazene, the weight ratio of which is (2-4):1; or, the electrolyte includes a mixture of ethoxyethoxyethyl acrylate and ethyl nitrate, the weight ratio of which is (1-4):1. The above-mentioned electrolyte additives act synergistically, which is more conducive to constructing a SEI membrane with both high lithium ion transport and structural stability, thereby being able to more significantly improve the fast charging capability and high temperature cycle performance of the secondary battery, reduce gas production, and enhance the safety of the battery.
[0108] The inventors further optimized the types and compositions of electrolyte additives. In a preferred embodiment, the electrolyte further includes other additives, including vinylene carbonate (VC), vinyl ethylene carbonate (VEC), lithium difluorophosphate (LiDFP), tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, 2,2,2-trifluoromethyl ethyl carbonate, 2,2,2-trifluorodiethyl carbonate, tris(trifluoroethyl) phosphate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, preferably one or more of vinylene carbonate, vinyl ethylene carbonate and lithium difluorophosphate. In a preferred embodiment, in the electrolyte, the weight percentage of other additives is 0.1-10%, preferably 0.1-5%. The above-mentioned other additives can participate in the formation of the SEI film, and cooperate with the ethoxy-containing additives and nitrogen-containing additives to construct a composite SEI film, which is more conducive to maintaining the structural integrity of the SEI film during fast charging, thereby further reducing electrolyte consumption and improving battery cycle life and safety.
[0109] In a preferred embodiment, the electrolyte further includes other lithium salts, and the other lithium salts include one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiOTF), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluoromalonate) borate (LiBFMB) and lithium difluorooxalatoborate (LiDFOB). The above-mentioned types of lithium salts can cooperate with the ethoxy-containing additives and nitrogen-containing additives of the present application to regulate the SEI film composition, further enhance the film stability and lithium ion conduction, inhibit side reactions, and jointly improve the battery fast charging capability, cycle life and safety.
[0110] Typically but not limiting, the weight percentage of other additives in the electrolyte is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two values.
[0111] In a preferred embodiment, the electrolyte further includes a solvent, and the solvent includes one or more of a chain carbonate, a cyclic carbonate and a carboxylic acid ester. Chain carbonates include one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and fluorinated chain carbonates; and / or, cyclic carbonates include one or more of ethylene carbonate, propylene carbonate and butylene carbonate; and / or, carboxylates include one or more of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorinated carboxylic acid esters. The above-mentioned types of solvents can cooperate with the additives of the present application to stabilize and evenly disperse the additives, which is more conducive to enhancing the effect of the additives, forming a more stable SEI layer, further reducing side reactions during battery cycling, improving the safety of the battery, and preventing thermal runaway caused by overcharging.
[0112] The inventors further optimized the type and composition of the positive electrode material. In a preferred embodiment, the positive electrode includes a positive electrode active material, the positive electrode active material includes a lithium nickel transition metal oxide, and the chemical formula of the lithium nickel transition metal oxide is: LiNi x Co y A (1-x-y) O2, wherein A includes one or more of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1, preferably, the lithium nickel transition metal oxide includes one or more of NCA, NCM333, NCM523, NCM622, NCM811, Ni90, Ni92 and Ni95. The stable and highly conductive interface layer formed by the additive of the present application can more effectively slow down the structural degradation of the above-mentioned positive electrode material during the charging and discharging process, thereby further extending the cycle life of the battery.
[0113] In a preferred embodiment, the positive electrode active material further comprises a phosphate compound, the chemical formula of the phosphate compound is LiMn k E (1-k) PO4, wherein 0≤k≤1, E comprises one or more of iron, cobalt, magnesium, calcium, zinc, chromium and lead, preferably, the phosphate compound comprises lithium iron phosphate, LiMn 0.6 Fe 0.4 PO4 or LiMn 0.8 Fe 0.2At least one of PO4. Typically but not limiting, k is 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a range consisting of any two values. The above-mentioned positive electrode active material can cooperate with the additive of the present application to optimize the SEI film structure, further enhance the diffusion of lithium ions, and is more conducive to improving the fast charging performance, cycle stability and safety of the battery, especially under high rate charge and discharge conditions, can more effectively inhibit the structural changes of the positive electrode material and extend the battery life.
[0114] In a preferred embodiment, the negative electrode active material in the negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon, silicon alloys, silicon oxide compounds, and silicon carbon compounds; preferably, in the negative electrode active material, the weight percentage of the silicon-based material is 10 to 100%. The additive of the present application can interact with the above-mentioned negative electrode active material to form a more stable SEI film, protect the negative electrode material from being corroded by the electrolyte, more effectively buffer the volume change of the silicon-based material during the charge and discharge process, and improve the conductivity of the negative electrode, thereby being more conducive to improving the charge and discharge efficiency, cycle stability, and safety of the battery.
[0115] The inventors further optimized the types and compositions of negative electrode materials. In a preferred embodiment, the negative electrode further includes one or more of carbon-based materials, metal materials and conductive polymers. Preferably, the carbon-based materials include one or more of natural graphite, artificial graphite, silicon-carbon composite materials (silicon-carbon or silicon-oxygen), lithium titanate, carbon black, acetylene black, Ketjen black and carbon fiber; and / or, the metal materials include one or more of copper, nickel, aluminum and silver, in the form of particles or fibers; and / or, the conductive polymer includes a polyphenylene derivative. The above-mentioned types of carbon-based materials are more conducive to the stable presence of nitrogen and oxygen elements in the SEI film, thereby further enhancing lithium ion conduction and inhibiting side reactions; the high conductivity of the above-mentioned types of metal materials combined with nitrogen-containing lithium salts can further accelerate lithium ion migration and improve fast charging efficiency; the above-mentioned types of conductive polymers can cooperate with additives to optimize the SEI film structure, further increase the film toughness, and reduce the interfacial impedance during the cycle, thereby further improving the cycle stability and energy density of the battery.
[0116] In a preferred embodiment, the positive electrode and / or the negative electrode further include a binder and / or a conductive agent. In a preferred embodiment, the binder includes one or more of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon. The above-mentioned types of binders can further improve the binding force between the active material particles, and are also conducive to improving the binding of the active material to the current collector.
[0117] In a preferred embodiment, the positive electrode further includes a positive electrode current collector, and the positive electrode current collector includes a metal foil and / or a composite current collector. Preferably, the metal foil includes aluminum foil; and / or the composite current collector is prepared by a process of forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate. In a preferred embodiment, the negative electrode further includes a negative electrode current collector, and the negative electrode current collector includes one or more of copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper and a polymer substrate coated with a conductive metal.
[0118] In a preferred embodiment, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator that can be used in the embodiment of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic material formed by a material that is stable to the electrolyte of the present application. The inorganic layer including inorganic materials includes inorganic particles and a binder, and the inorganic particles include one or more of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate; and / or, the binder includes one or more of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer including the polymer includes the polymer including one or more of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0119] In a preferred embodiment, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes one or more of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.
[0120] Typically but not limiting, in lithium nickel transition metal oxides, x is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a range consisting of any two values, and y is 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range consisting of any two values.
[0121] In a preferred embodiment, the preparation method of a secondary battery includes providing an electrode assembly, injecting, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, such as 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C. In a preferred embodiment, the pressure of the formation is 150 to 250kgf, such as 160kgf, 170kgf, 180kgf, 190kgf, 200kgf, 210kgf, 220kgf, 230kgf or 240kgf. In a preferred embodiment, the charging current of the formation is 0.05 to 0.1C, and the discharge current is 0.1 to 0.3C. In a preferred embodiment, the formation comprises: charging to 4.2V with a current of 0.05C and standing for 60 minutes at a temperature of 40-50°C, preferably 45°C, and a pressure of 150-250kgf, preferably 200kgf, followed by charging to 4.2V with a current of 0.1C, and then discharging to 3.0V with a current of 0.2C.
[0122] If the charge current or discharge current of the formation is too large, the temperature inside the battery may rise rapidly, thereby increasing the risk of overheating the battery, which may damage the performance and life of the battery, and may also cause the chemical reaction inside the battery to be unstable, affecting the battery's charge and discharge efficiency and energy density. If the charge current or discharge current of the formation is too small, the production efficiency is low, and the electrochemical performance, cycle life and safety performance of the battery will be reduced. If the formation pressure is too high, the electrode structure of the battery may be deformed or damaged, and the internal chemical reaction may not proceed sufficiently, which may lead to reduced electrochemical performance of the battery and even safety problems. If the pressure is too low, it may cause poor contact between the positive and negative electrodes, local overheating of the battery, and increased resistance, which may affect the performance, life and safety of the battery.
[0123] In a preferred embodiment, the secondary battery is a lithium secondary battery or a sodium secondary battery. In a preferred embodiment, the lithium secondary battery includes one or more of a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery and a lithium ion polymer secondary battery.
[0124] In a preferred embodiment, the secondary battery includes an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; and / or, the outer package may be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS). In a preferred embodiment, the shape of the secondary battery is not particularly limited, and it may be cylindrical, square or any other shape.
[0125] In a preferred embodiment, the present application also provides a battery module, including the above-mentioned secondary battery. The battery module of the present application adopts the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The battery module of the present application may contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0126] In a preferred embodiment, the present application further provides a battery pack, comprising the above-mentioned battery module. The number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0127] In another typical embodiment of the present invention, there is also provided an electric device, including the above-mentioned secondary battery. The electric device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. The electric device using the secondary battery of the present application can enhance the fast charging and cycling performance of the electric device through the optimized SEI film, significantly improve the overall energy density, power output and durability, and is suitable for application scenarios requiring high energy, fast charging and long-term stable operation. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used. The electric device can also be a mobile phone, a tablet computer, a laptop computer, etc. The electric device is light and thin, and a secondary battery can be used as a power source.
[0128] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0129] Example 1
[0130] The steps for preparing the positive electrode sheet are as follows: according to the weight ratio of positive electrode active material: conductive agent: binder = 95:3:2, weigh the positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 A mixture of O2, conductive carbon nanotubes and acetylene black (the weight ratio of the two is 2:1), and a binder polyvinylidene fluoride PVDF are fully slurried in an N-methylpyrrolidone NMP solvent system, coated on a 12μm thick aluminum-coated current collector, dried, and rolled to obtain a positive electrode sheet.
[0131] The steps of preparing the negative electrode sheet are as follows: according to the weight ratio of negative electrode active material: conductive agent: binder: thickener: polyacrylic acid = 95:2:1.5:1:0.5, the negative electrode active material silicon oxide (SiO x , x=1)-graphite composite (the weight ratio of silicon oxide to graphite in the composite is 14:86), conductive agent acetylene black, binder styrene-butadiene rubber SBR, thickener sodium carboxymethyl cellulose CMCNa, and polyacrylic acid PAA are fully slurried in deionized water and then coated on the surface of 8μm thick copper current collector. After drying, rolling and stripping, the negative electrode pole piece is obtained, wherein the negative electrode rolling line load is 470N / mm, it is a secondary rolling method, the rolling temperature is 120℃, the rolling speed is 2min / m, and the tortuosity of the obtained negative electrode pole piece is 6.2.
[0132] Diaphragm: PP / PE / PP three-layer composite diaphragm.
[0133] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), lithium salt LiPF6 and solvent EC / DMC / EMC = 25 / 20 / 55 are mixed evenly to prepare a 1M solution, and finally an ethoxylated compound additive (EOEA, the weight percentage in the electrolyte is 1%) and a nitrogen-containing compound additive (LiFSI, the weight percentage in the electrolyte is 3.5%) are added, and the electrolyte is obtained after stirring evenly.
[0134] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrode sheets, and wind them to obtain a bare battery cell; place the bare battery cell in an aluminum-plastic film outer package, inject the prepared lithium-ion battery electrolyte after sufficient drying, and the battery is left at 45°C for 48h, formed in a high-temperature fixture (formation conditions are: temperature 45°C, pressure 200kgf, 0.05C current charged to 4.2V and allowed to stand for 60min, then 0.1C charged to 4.2V, then 0.2C discharged to 3.0V, and so on, repeated twice) and secondary sealing, and then perform conventional capacity division to obtain a secondary battery-lithium-ion battery.
[0135] Examples 2 to 11
[0136] The only difference from Example 1 is:
[0137] The composition of the electrolyte is different, see Table 1 for details.
[0138] Examples 12 to 18
[0139] The only difference from Example 1 is:
[0140] The composition of the electrolyte is different, and the preparation process parameters of the battery are different, see Table 1 for details.
[0141] Comparative Example 1
[0142] The only difference from Example 8 is that no ethoxylated additive is included.
[0143] Comparative Example 2
[0144] The only difference from Example 8 is that no nitrogen-containing additive is included.
[0145] Comparative Example 3
[0146] The only difference from Example 8 is that the content of nitrogen-containing additive is too high, see Table 1 for details.
[0147] Comparative Example 4
[0148] The only difference from Example 8 is that the content of the ethoxylated additive is too high, see Table 1 for details.
[0149] Comparative Examples 5 to 6
[0150] The only difference from Example 8 is that in the preparation step of the negative electrode sheet, the rolling line load of the negative electrode sheet is different. The tortuosity of the negative electrode sheet is different, see Table 1 for details.
[0151] Comparative Examples 7 to 13
[0152] The only difference from Example 8 is that in the formation step of preparing the secondary battery, the process parameters are different, see Table 1 for details.
[0153] Some components and parameters of the secondary batteries prepared in the above examples and comparative examples, as well as the preparation process parameters are shown in Table 1, and the performance parameter test results of the secondary batteries are shown in Table 2.
[0154] Test method:
[0155] 1. Determination of pole piece tortuosity:
[0156] The tortuosity of the electrode piece can be obtained by image recognition and analysis, specifically: first take a morphological picture of the electrode surface through a scanning electron microscope SEM, then import it into the Wolfram Mathmatica software, run the tortuosity index estimation code file CDF, calibrate the contour of the active material particles in the surface photo, click the Fit button, calculate the a, b, c three-axis characteristics and particle orientation angle of the calibrated particles, click the Calculate button, and calculate the tortuosity index aX, aY, aZ in the XYZ directions, where the aZ value is the tortuosity index of the electrode piece, and the tortuosity τ = ε -aZ .
[0157] Among them, ε is the porosity of the electrode, which is measured by a mercury intrusion instrument. Specifically, the dried electrode sample is cut into thin strips of a certain size, and the apparent volume of the electrode coating is measured using a micrometer. The apparent volume = sample coating thickness × sample length × sample width. The electrode is then vacuum degassed, rolled and placed in a sample cell, ensuring that the sample volume is 40-70% of the effective volume of the sample tube to ensure measurement accuracy. The pore volume of the sample is then measured using a mercury intrusion instrument, that is, the volume of mercury pressed into the sample, and the porosity ε = pore volume / apparent volume.
[0158] 2. Battery internal resistance test:
[0159] The lithium-ion battery is discharged at 1C constant current to a cut-off voltage of 3.0V, and after being placed at 20±2℃ for 1h, it is charged at 1C current for 18min, the SOC is adjusted to 30%, and placed for 1h, and then charged at 3C current for 1.5min, and placed for 1h, and then discharged at 9C current for 0.5min, and placed for 1h, and then charged at 1C constant current for 6min, and the SOC is adjusted to 40%, and placed for 1h. This cycle is repeated until the SOC is tested to be 70%, and the battery DC resistance DCR value is calculated by the formula R=ΔU / ΔI.
[0160] 3. Battery cycle capacity retention rate test:
[0161] At 25°C, the lithium-ion battery was charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V, and then discharged to 2.5V at 2C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 25°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle × 100%.
[0162] At 45°C, the lithium-ion battery was charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V, and then discharged to 2.5V at 2C constant current. After 400 cycles of charge and discharge, the capacity retention rate after the 400th cycle at 45°C was calculated according to the following formula: discharge capacity after the 400th cycle / discharge capacity of the first cycle × 100%.
[0163] 4. Battery 45℃ storage thickness change rate test:
[0164] The battery was discharged at 0.5C constant current to 3.0V at 25°C, then charged at 0.5C constant current to 4.45V, and then charged at 4.45V constant voltage to 0.05C. The thickness of the battery at this time was measured using a PPG soft pack battery thickness gauge and recorded as a. The battery was placed in an oven and stored at 45°C at a constant voltage of 4.45V for 15 days. The thickness after 15 days was recorded as b. The thickness expansion rate was calculated as: (ba) / a×100%.
[0165] 5. Test of oxygen and nitrogen content in SEI film:
[0166] The lithium-ion battery was discharged to 2.5V at a current of 0.1C, and the lithium-ion battery was disassembled in a glove box filled with argon to obtain the electrode sheet. The obtained positive electrode sheet was cut into a test sample of 8mm×8mm size, and soaked and cleaned with a low-boiling dimethyl carbonate (DMC) solvent for half an hour. After being completely dried, it was pasted on the XPS sample stage, with the surface of the positive electrode active material layer facing away from the current collector facing upward, and the measurement was performed without exposure to the atmosphere.
[0167] The specific test conditions and steps are as follows: using single crystal spectrum AlKα rays, as for the X-ray point, using an elliptical form of 1000×1750μm with an output of 10KV and 22mA, selecting the data when the sputtering etching time is 0 seconds, using 284.8eV for neutral carbon C1s, and as for data processing such as peak differentiation, using 3-point smoothing, peak area measurement, background subtraction and peak synthesis to calculate the weight percentage of oxygen elements in ethoxy compounds contained in the SEI film and nitrogen elements in lithium nitride contained in the SEI film.
[0168] Table 1
[0169]
[0170]
[0171]
[0172]
[0173] Table 2
[0174]
[0175]
[0176] From the above, it can be seen that compared with the comparative example, the embodiment of the present invention controls the type of electrolyte in the secondary battery, and controls the contents of nitrogen and oxygen in the solid electrolyte interface film (SEI film) formed on the surface of the negative electrode active material layer within a specific range, so that the SEI film has a fast lithium ion transmission speed while being able to remain dense and stable, effectively suppressing the continuous side reactions caused by the contact between the electrolyte and the negative electrode active material and the consumption of the electrolyte, thereby extending the cycle life of the secondary battery.
[0177] Specifically, the nitrogen-containing compounds and ethoxy-containing compounds from the electrolyte in SEI can quickly transport lithium ions and reduce impedance, thereby improving the fast charging performance and low-temperature performance of the battery; in addition, the nitrogen-containing compounds and ethoxy-containing compounds have a good synergistic effect in structure, further improving the density and flexibility of the SEI film, thereby effectively inhibiting the rupture of the SEI film during high-temperature cycling, thereby reducing the negative effects of continuous side reactions between the electrolyte and the negative electrode, and extending the cycle performance of the secondary battery, especially the cycle life and storage performance at high temperatures. Based on the above improvements, the secondary battery of the present invention has excellent fast charging performance, and at the same time, has good cycle performance, storage performance and safety performance at high and low temperatures.
[0178] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the comprehensive performance of the secondary battery is better.
[0179] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A secondary battery, characterized in that: Including positive electrode, negative electrode and electrolyte, The electrolyte includes an ethoxy-containing additive and a nitrogen-containing additive; The negative electrode comprises a negative electrode active material layer, and a solid electrolyte interface film located on the surface of the negative electrode active material layer, wherein the solid electrolyte interface film contains an ethoxy compound and lithium nitride, wherein the ethoxy compound is derived from the ethoxy-containing additive, and the lithium nitride is derived from the nitrogen-containing additive; The weight percentage of oxygen element from the ethoxy compound in the solid electrolyte interface film is defined as W O %, and the weight percentage of nitrogen element from the lithium nitride in the solid electrolyte interface film is defined as W N %, where 3≤2W O +W N ≤10.
2. The secondary battery according to claim 1, characterized in that: 0.05<W O <5, preferably, 1≤W O ≤3; and / or, 1<W N <10, preferably, 2≤W N ≤8.
3. The secondary battery according to claim 1 or 2, characterized in that: The tortuosity of the negative electrode is defined as τ, where 0 < 2 (W N ×W O )-τ<1.
4. The secondary battery according to claim 3, characterized in that: 2.5<τ<9.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The ethoxy-containing additive includes one or more of ethoxy acrylate, ethoxy vinylene carbonate and ethoxy vinylene sulfite; Preferably, the ethoxy acrylate has a structure shown in general formula (I-1): In the general formula (I-1), n is an integer from 1 to 4, R 11 is selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate, R 12 Selected from hydrogen, C1-C3 alkyl; Preferably, the ethoxy vinylene carbonate has a structure shown in general formula (I-2): In the general formula (I-2), m is an integer from 1 to 4, and R 13 Selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate; Preferably, the ethoxy vinylene sulfite has a structure shown in general formula (I-3): In the general formula (I-3), p is an integer from 1 to 4, R 14 Selected from hydrogen, C1-C3 alkyl, vinyl carboxylate or propenyl carboxylate; and / or, The nitrogen-containing additive includes one or more of nitrile compounds, phosphazenes, amides, organic nitrogen-containing lithium salts, inorganic nitrogen-containing alkali metal salts, nitrate esters and nitroesters; Preferably, the nitrile compound has a structure represented by the general formula (II-1): N≡CR 21 -R 22 General formula (II-1); In the general formula (II-1), R 21 is selected from C2-C10 alkylene or nitrile-substituted C2-C10 alkylene, R 22 is selected from hydrogen, nitrile, C1-C6 alkyl or carboxylate; Preferably, the phosphazene has a structure shown in general formula (II-2): In the general formula (II-2), R 23 is selected from C1-C6 alkyl or fluorinated C1-C6 alkyl, R 24 , R 25 , R 26 , R 27 and R 28 are independently selected from hydrogen, fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 24 , R 25 , R 26 , R 27 and R 28 At least one of them is fluorine or fluorinated C1-C6 alkyl; Preferably, the amide has a structure represented by general formula (II-3): In the general formula (II-3), R 29 , R 210 , R 211 are independently selected from hydrogen, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 29 , R 210 , R 211 At least one of them is a fluorinated C1-C6 alkyl group; Preferably, the organic nitrogen-containing lithium salt has a structure represented by general formula (II-4) or general formula (II-5): In the general formula (II-4), R 212 , R 213 , R 214 are independently selected from hydrogen, fluorine, C1-C6 alkyl, fluorinated C1-C6 alkyl or nitrile, and R 212 , R 213 , R 214 At least one of them is selected from fluorine, fluorinated C1-C6 alkyl or nitrile; In the general formula (II-5), R 215 , R 216 are independently selected from fluorine, C1-C6 alkyl or fluorinated C1-C6 alkyl, and R 215 and R 216 At least one of them is selected from fluorine or fluorinated C1-C6 alkyl; Preferably, the inorganic nitrogen-containing alkali metal salt has a structure shown in general formula (II-6): R 217 NO t General formula (II-6); In the general formula (II-6), t is selected from 2 or 3; R 217 Selected from lithium, sodium or potassium; Preferably, the nitrate ester has a structure shown in general formula (II-7): R 218 NO r General formula (II-7); In the general formula (II-7), r is 3; R 218 Selected from C1-C4 alkyl; Preferably, the nitroester has a structure shown in the general formula (II-8): R 219 NO s General formula (II-8); In the general formula (II-8), s is 2; R 219 Selected from C1~C4 alkyl.
6. The secondary battery according to claim 5, characterized in that: The ethoxy acrylate includes one or more of ethoxyethoxyethyl acrylate, 2-methoxyethyl acrylate and triethylene glycol diacrylate; and / or, The ethoxy vinylene carbonate includes one or more of methylethoxy vinylene carbonate, methylethoxy vinylene sulfite and methoxyethoxymethyl vinylene carbonate; and / or, The ethoxy vinylene sulfite includes ethoxymethyl vinylene sulfite; and / or, The nitrile compound includes one or more of succinonitrile, adiponitrile, glutaronitrile, hexanetrinitrile, ethylene glycol (bis) propionitrile ether, methoxypropionitrile, 2,3-dimethoxypropionitrile and methyl cyanoacetate; and / or, The phosphazene includes one or more of methoxypentafluorocyclotriphosphazene, trifluoromethoxypentafluorocyclotriphosphazene, ethoxypentafluorocyclotriphosphazene and trifluoroethoxypentafluorocyclotriphosphazene; and / or, The amide comprises trifluoroformamide or trifluoroacetamide; and / or, The organic nitrogen-containing lithium salt includes one or more of 4,5-dicyano-2-(trifluoromethyl)imidazolium lithium, (fluorosulfonyl) (perfluorobutylsulfonyl) imide lithium, bis (fluorosulfonyl) imide lithium, bis (trifluoromethylsulfonyl) imide lithium and bis (pentafluoroethylsulfonic acid) imide lithium; and / or, The inorganic nitrogen-containing alkali metal salt includes one or more of lithium nitrate, lithium nitrite, sodium nitrate and sodium nitrite; and / or, The nitrate ester includes ethyl nitrate and / or propyl nitrate; and / or, The nitroesters include nitromethane and / or nitroethane.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: In the electrolyte, the weight percentage of the ethoxylated additive is 0.05-4%; and / or, In the electrolyte, the weight percentage of the nitrogen-containing additive is 0.5-10%; Preferably, the weight ratio of the ethoxy-containing additive to the nitrogen-containing additive is (0.05-4):
1.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte comprises a mixture of ethoxyethoxyethyl acrylate and lithium bis(fluorosulfonyl)imide, the weight ratio of the two being (0.05-4):1; or, The electrolyte comprises a mixture of ethoxyethoxyethyl acrylate and ethoxypentafluorocyclotriphosphazene, the weight ratio of the two being (2-4):1; or, The electrolyte includes a mixture of ethoxyethoxyethyl acrylate and ethyl nitrate, and the weight ratio of the two is (1-4):
1.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte further comprises other additives, which include one or more of vinylene carbonate, vinyl ethylene carbonate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, 2,2,2-trifluoromethyl ethyl carbonate, 2,2,2-trifluorodiethyl carbonate, tris(trifluoroethyl)phosphate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether; in the electrolyte, the weight percentage of the other additives is 0.1-10%; and / or, The positive electrode includes a positive electrode active material, the positive electrode active material includes a lithium nickel transition metal oxide, and the chemical formula of the lithium nickel transition metal oxide is: LiNi x Co y A (1-x-y) O2, wherein A comprises one or more of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; and / or, The negative electrode active material in the negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon, silicon alloys, silicon oxides and silicon carbon compounds; preferably, in the negative electrode active material, the weight percentage of the silicon-based material is 10-100%.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Non-aqueous electrolyte for lithium secondary battery and lithium secondary battery comprising same
CN103348526A
Lithium secondary battery electrolyte with high and low temperature performance and lithium secondary battery
CN115832436A
Electrolyte composition for lithium metal battery
CN116583980A
Secondary battery and electric device
CN118367108A
Negative pole piece, preparation method thereof and battery
CN119252918A
Cited By
Secondary battery and electrical apparatus
WO2026149028A1